Pengaruh Pola Asuh Orang Tua dan Bimbingan Guru Terhadap Kemandirian Sosial Emosional Anak Usia Dini - Laili Rahmatika; Anita Damayanti (Jurnal Studi Guru dan Pembelajaran, 2023)
The purpose of this research is to examine how social and emotional autonomy of early childhood is influenced by the directions of parents and educators. This study is an example of a quantitative research design. This study triangulated interviews, observations, documents, and questionnaires. This study uses analysis/processing of partial correlation data. Participants consisted of both parents and educators from the Batam City Aisyiyah play group. Grade 4-5 students were deliberately selected as the research sample. This study involved three play groups with 90 students. The data collection was based on a questionnaire. The research findings show that there is an effect of giving a teacher's effectiveness guidance in learning to teachers in the classroom by 42.46%, and appropriate provision in the direction of educators by 41.47% in the classroom environment, then the help of parents and teachers has a positive impact the large effect on students' social emotional independence resulted in a Fregression value of 75.168, and there was a 63.9% combination of parenting methods and teacher directions affecting students' social and emotional independence. This study concluded that (1) authoritarian parenting style has a negative effect on children's emotional social autonomy. Teacher influence on students' social and emotional independence capacity Early childhood social and emotional independence is influenced by (3) parental practices and teacher instructions. Then this study found that parental style and teacher direction had a significant effect on children's social and emotional autonomy in kindergarten.